An overview of evaluating the efficacy of microbial pathogens for biological control of the red palm weevil Rhynchophorus ferrugineus (Olivier, 1790) (Coleoptera: Curculionidae) insights from laboratory and field studies - Koko Dwi Sutanto; Catur Raharjo Febrayanto; Wiratno Wiratno; Dwinita Wikan Utami; Fitri Susiyanti; Mohammad Agus Yulianto; Araz Meilin; Iwa Mara Trisawa (Egyptian Journal of Biological Pest Control)
Abstract Background This overview explores the use of entomopathogenic nematodes (EPNs), fungi (EPFs), bacteria (EPBs), and viruses (EPVs) as biological control strategies against the red palm weevil (RPW) (Rhynchophorus ferrugineus), a significant pest of date palms in Saudi Arabia. Laboratory and field studies have evaluated the efficacy of these pathogens, which employ different infection mechanisms to manage RPW populations. The review aims to provide insights into the pathogenicity and application methods of these microbial agents, supporting the development of sustainable integrated pest management strategies for date palm cultivation. Results The results indicate that entomopathogenic nematodes (EPNs), fungi (EPFs), bacteria (EPBs), and viruses (EPVs) are effective microbial agents for controlling the red palm weevil (RPW), a significant pest of date palms in Saudi Arabia. Laboratory and field studies have demonstrated their efficacy, utilizing different infection mechanisms to manage RPW populations at various life stages. However, limitations exist, including a lack of comprehensive research on certain microbial pathogens and the need for further studies to optimize application methods and environmental adaptability. These gaps highlight the importance of this review in synthesizing findings and providing a solid foundation for future research on sustainable integrated pest management strategies for RPW control. Conclusion This overview underscores the potential of entomopathogenic microorganisms as effective biocontrol agents against the red palm weevil, emphasizing their role in sustainable pest management strategies. Continued research is essential to address existing gaps and optimize the application of these microbial agents in date palm cultivation.